2006
DOI: 10.1111/j.1083-6101.2006.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Homophily of Network Ties and Bonding and Bridging Social Capital in Computer-Mediated Distributed Teams

Abstract: This research studied homophily of network ties in distributed teams in both task‐related instrumental networks and non‐task related expressive networks. Homophily of network ties was examined in terms of demographic and social characteristics, including gender, race, geographic location, and group assignment. Social network data were collected from 32 students enrolled in a distance learning class from two universities. MQAP regression analysis showed that homophily in gender and in race had no significant im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 50 publications
2
98
0
1
Order By: Relevance
“…Barab, MaKinster, and Scheckler (2003) noted that proximity in terms of physical location influenced whether members of work teams collaborated with each other, even when team members were spread out over geographic distances and were working together through online collaborative tools. Huang, Shen, and Contractor (2013) reported similar findings in terms of proximity among members of gaming communities, while Yuan and Gay (2006) found that proximity as well as other shared sociodemographic characteristics influenced network ties even among individuals who have only interacted through computer-mediated communication.…”
Section: Introductionmentioning
confidence: 83%
“…Barab, MaKinster, and Scheckler (2003) noted that proximity in terms of physical location influenced whether members of work teams collaborated with each other, even when team members were spread out over geographic distances and were working together through online collaborative tools. Huang, Shen, and Contractor (2013) reported similar findings in terms of proximity among members of gaming communities, while Yuan and Gay (2006) found that proximity as well as other shared sociodemographic characteristics influenced network ties even among individuals who have only interacted through computer-mediated communication.…”
Section: Introductionmentioning
confidence: 83%
“…Z pewnością zaś wpływają na ogólną aktywność życiową młodych ludzi, modyfikując charakter interakcji społecznych, ogólną postawę życiową czy nastawienia wobec przyszłości (Arnett 2000(Arnett , 2004(Arnett , 2006Czerwińska-Jasiewicz 1991, 1996. Należy jednak podkreślić, że to przede wszystkim indywidualna interpretacja rzeczywistości kształtuje postawy i nastawienia, w większym stopniu niż jej faktyczny stan (Denscombe 1993;Giddens 1999;Harpham, Grant, Thomas 2002;Palich, Ray Bagby 1995;Ramirez-Sanchez, Pinkerton 2009;Saunders, Strock, Travlos 1990;Voicu 2005;Walesa 1988;Yuan, Gay 2006). Indukowanie zagrożeń może prowadzić do nasilonego odczuwania niepewności i związanego z tym stresu (Beck 1986(Beck , 1992(Beck , 2004Giddens 1999Giddens , 2001Renn 1998;Rossa 2010).…”
Section: Wprowadzenieunclassified
“…Cultural distance presents two boundaries, distance and culture that presents critical discontinuities to manage for effectiveness of global organizational contexts (Cogburn & Levinson, 2003, Watson-Manheim, Chudoba, & Crowston, 2002, and constraints to be overcome (Yuan & Gay, 2006). Under the assumption that the economy gains from labor division, differentiation and collective efficiency on firms of one sector cluster between each other developing specialized knowledge reinforced through a common organizational culture (Young, 1928).…”
Section: Implications Of Culture In Strategy Of Multinational Firmsmentioning
confidence: 99%